The Effect of Stock Liquidity on Companies Future Investment: A Study of the Iranian Capital Market - Zahra Nadafi; Mohammd Reza Pourali (مدیریت نوآوری و راهبردهای عملیاتی)
Purpose: This study aimed to measure the impact of stock liquidity on future investment in companies listed on the Tehran Stock Exchange. Methodology: 95 companies from 2012-2019 were selected as the study's sample size for this purpose. The research method is descriptive correlation and multiple regression using the panel-data method to estimate the regression model with panel data and for analysis. Findings: This study showed that stock liquidity negatively and significantly affects the company's future investment. The results show no significant difference between stock liquidity and corporate future investment in large and small companies and companies with information symmetry and information asymmetry. Originality/Value: The size of companies and the speed of information dissemination in the market do not affect the relationship between stock liquidity and future investment, and the market reacts to any information.